2016
DOI: 10.1109/jbhi.2015.2403283
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and Jugular Classification in ARTSENS

Abstract: Over past few years our group has been working on the development of a low-cost device, ARTSENS, for measurement of local arterial stiffness (AS) of the common carotid artery (CCA). This uses a single element ultrasound transducer to obtain A-mode frames from the CCA. It is designed to be fully automatic in its operation such that, a general medical practitioner can use the device without any prior knowledge of ultrasound modality. Placement of the probe over CCA and identification of echo positions correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A recent study has reported that the JVP waveform contains important prognostic information regarding heart failure [1,21]. We expect that use of the proposed method in acquisition of accurate JVP waveform information will contribute to the diagnosis of such pathologies.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study has reported that the JVP waveform contains important prognostic information regarding heart failure [1,21]. We expect that use of the proposed method in acquisition of accurate JVP waveform information will contribute to the diagnosis of such pathologies.…”
Section: Discussionmentioning
confidence: 95%
“…Because the Vicorder uses a neck pressure pad placed over the carotid area, interference of the jugular vein on the arterial signal is known to be present [20]. Accordingly, the manufacturer's instructions recommend the measurements to be done in the upper body tilted position (at ∼30°).…”
Section: Methodsmentioning
confidence: 99%
“…The a, c and v waves are well visible in the CSA time diagram, as well the P, Q, R, S and T waves in the ECG. The CSA time diagram actually corresponds with the well known JVP diagram (Sisini et al, 2015;Sahani et al, 2015). The relationship between the ECG and CSA time diagram (JVP waves) is the following: the R wave is just after the a wave and before the c wave.…”
Section: Cross Sectional Area Velocity and Ecg Datasets Acquisitionmentioning
confidence: 98%